Parents-child multiple sites of microbial and metabolic signatures in autism spectrum disorder - Zhu, Lingping; Zhang, Haiyan; Tang, Meiling; Yang, Xuefeng; Chen, Yongjun (Frontiers in Microbiology, 2026)
IntroductionTo investigate the horizontal transmission of oral-gut microbiota in autism spectrum disorder (ASD) families and its potential implications for ASD pathogenesis.MethodsThe research employed a paired cohort design using family cohorts (23 ASD children/17 parents vs. 18 Non-ASD children/16 parents), conducting integrated microbiome and metabolomic analyses of oral and fecal samples.ResultsThe findings revealed that ASD families exhibited significantly increased oral microbial species diversity alongside substantial alterations in gut microbiota composition, particularly demonstrating a lower Firmicutes/Bacteroidetes ratio (3.60/2.97) compared to Non-ASD families (5.59/5.35). Specific microbial changes included notable enrichment of Prevotella_9 in ASD gut microbiota. Metabolomic profiling identified significant disruptions in multiple metabolic pathways, including impaired L-rhamnose degradation and glutathione metabolism. The study observed coordinated oral-gut axis alterations through synchronized changes in Caulobacter and Serratia abundances, suggesting a distinct dysbiotic pattern along this microbial continuum. Additional metabolic findings demonstrated reduced levels of fecal glutamine and Ala-Gly in ASD children, with glycylproline exhibiting high predictive value for family typing (AUC = 0.91). Integrative analysis further revealed significant correlations between Holdemanella and various lipid metabolites.DiscussionIt indicates that ASD families display characteristic oral-gut microbiota interactions accompanied by metabolic abnormalities, potentially reflecting familial microbial transmission patterns that may contribute to ASD pathophysiology.